Tracing the function expansion for a primordial protein fold in the era of fold-based function prediction: β-trefoil - Moushmi Goswami; Subhashini Srinivasan (PLoS ONE, 2025)
The incredibly narrow protein fold bottleneck, which separates the billions of unique proteins on one side to deliver diverse biological functions on the other, arises from folds that tolerate mutations during evolution. One such fold, called the β-trefoil, is present in functionally diverse proteins including cytokines involved in the immune system such as interleukin-1. The unrecognizable sequence-level diversity, even among paralogs of interleukin-1 within the same chromosomal locus, suggests the resilience of this fold to mutational onslaught. Furthermore, β-trefoil domain containing-proteins are known to coexist with other domains to achieve functional diversity. In this study, we challenge the reach and limitations of function prediction using fold-fold comparison using β-trefoil fold as an example. We identified proteins containing β-trefoil fold belonging to thirty-two distinct functional classes based on diverse domain architecture and/or functional annotation by mining both the PDB and AlphaFold databases using fold-fold comparison. Among the proteins with novel domain architecture we find β-trefoil along with chitinase, lipase, β-glucosidase, protein kinase, peptidoglycan-binding + peptidase matrixin, glycosyl hydrolases family 3 + PA14 + fibronectin type- III, alpha galactosidase A, PhoD-like phosphatase, insecticidal crystal toxin, trypsin, alginate lyase and two novel structurally uncharacterized domains. We demonstrate that fold-fold comparison can extend function prediction beyond the reach of sequence-based approach and provides an opportunity to discover novel domain architecture associated with known folds. However, since extending fold similarity to functional similarity may be challenged by convergent fold evolution, we explore if β-trefoil may be a convergent evolution and share our hypothesis.